IMPLEMENTASI PROGRAM LIFE SKILL SMA INTENSIF TERHADAP PERKEMBANGAN PESERTA DIDIK DI YAYASAN PONDOK PESANTREN MODERN NURUL IKHLAS PADANG PANJANG - Adra, Silnia; Melia, Yenni; Yatim, Yenita (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
Implementation is the application in an activity to achieve activity objectives based on certain norms so that the activity can run effectively. In the Nurul Ikhlas Modern Islamic Boarding School there is one program that is running, namely the life skills program. Based on the phenomena found in the field when making observations, namely the existence of this life skill program was formed due to the limited space for students to move. Therefore this study aims to describe the implementation of the Intensive High School life skills program on the development of students at the Nurul Ikhlas Padang Panjang Modern Islamic Boarding School Foundation. The theory used in this research is Structural Functional Theory according to Parsons. The approach used is qualitative with a descriptive research type. Data collection techniques used in this research are observation, interviews, and document studies. Selection of informants in this study through purposive sampling technique. With the number of informants 12 people. The unit of analysis in this study is the individual. Data analysis used in this study used 4 steps, namely: data collection, data reduction, data presentation and drawing conclusions. This research was conducted at Nurul Ikhlas Panjang Panjang Intensive High School. The results of this study indicate that the implementation of the life skill program at Nurul Ikhlas Padang Panjang Intensive High School on the development of students, namely: students are able to develop creativity in processing food ingredients and foster an entrepreneurial spirit in the field of culinary arts, students are able to improve literacy and creativity in writing in the field of journalism , students are able to increase self-confidence and skills in playing music in the field of music and students are able to build creativity, motor skills, and express themselves in the field of craft.